The impact of a holistic admissions process on college math completion rates at a Wisconsin technical college - Stancher, Amber L. (University of Wisconsin--Stout, 2019)
The purpose of this study was to research whether the new admissions process at Mid-State Technical College had an impact on College Math completion rates for students who would have been referred to remedial coursework under previous policies. It also examined the impact of supplemental instruction attendance on completion rates. Prior to this research, Mid-State had not completed an internal data review to assess the effectiveness of the admission policy on predicting the success of students directly placed into College Math and the effectiveness of the supplemental course instruction. Ex post facto data from the Fall 2018 and Spring 2019 semesters was used to complete this research, including Accuplacer/ACT math scores, College Math grade rosters, and student attendance records. Pearson correlation analysis was used to identify if relationships existed between the data selected for this study and successful course completion. Results of the study indicated that students directly enrolled in College Math based on their high school transcript had a slightly higher completion rate than students enrolled based on meeting the Accuplacer/ACT cut score. Additionally, students enrolled based on high school data who regularly attended the additional hour of instruction had higher completion rates than students who did not attend.
Keywords: Technical institutes; Universities and colleges; Mathematics